Crystallization‐Driven Self‐Assembly of Rod–Coil–Rod Pseudopolyrotaxanes into Spherical Micelles, Nanorods, and Nanorings in Aqueous Solutions. Issue 15 (20th May 2015) - Qi, Rui; Jin, Yong; Cheng, Xinfeng; Fan, Baozhu; Sun, Tongbing; Peng, Shaojun; Li, Hanping
<x xml:space="preserve">Abstract</x> A novel rod‐containing block copolymer is constructed by supramacromolecular self‐assembly of α‐cyclodextrin and a triblock copolymer with methoxy polyethylene glycol as the flanking chains and the midterm block alternately connected by 2, 2‐dimethylolbutyric acid and isophorone diisocyanate. The assembled rod‐containing block copolymer shows an exciting phenomenon of concentration‐ and pH‐dependent morphological switching of well‐defined nanostructures. In the solutions at pH 9.2, spherical micelles, rod‐like micelles, and hydrogel are observed successively with an increase of the concentration. Notably, the rod‐like micelles are composed of spherical segments due to the combination of the crystalline cores of the spherical micelles. In addition, 1D nanostructures with different curvatures from linear rod‐like micelles (pH 9.2) to ring‐shaped micelles (pH 7.5) can be obtained by controlling the pH values of the assembled systems.